Alterations in GABA-related transcriptome in the dorsolateral prefrontal cortex of subjects with schizophrenia - Hashimoto, T; Arion, D; Unger, T; Maldonado-Avilés, J G; Morris, H M; Volk, D W; Mirnics, K; Lewis, D A (Molecular psychiatry, 2008)
In subjects with schizophrenia, impairments in working memory are associated with dysfunction of the dorsolateral prefrontal cortex (DLPFC). This dysfunction appears to be due, at least in part, to abnormalities in γ -aminobutyric acid (GABA)-mediated inhibitory circuitry. To test the hypothesis that altered GABA-mediated circuitry in the DLPFC of subjects with schizophrenia reflects expression changes of genes that encode selective presynaptic and postsynaptic components of GABA neurotransmission, we conducted a systematic expression analysis of GABA-related transcripts in the DLPFC of 14 pairs of schizophrenia and age-, sex- and post-mortem interval-matched control subjects using a customized DNA microarray with enhanced sensitivity and specificity. Subjects with schizophrenia exhibited expression deficits in GABA-related transcripts encoding (1) presynaptic regulators of GABA neurotransmission (67 kDa isoform of glutamic acid decarboxylase (GAD 67 ) and GABA transporter 1), (2) neuropeptides (somatostatin (SST), neuropeptide Y (NPY) and cholecystokinin (CCK)) and (3) GABA A receptor subunits ( α 1, α 4, β 3, γ 2 and δ ). Real-time qPCR and/or in situ hybridization confirmed the deficits for six representative transcripts tested in the same pairs and in an extended cohort, respectively. In contrast, GAD 67 , SST and α 1 subunit mRNA levels, as assessed by in situ hybridization, were not altered in the DLPFC of monkeys chronically exposed to antipsychotic medications. These findings suggest that schizophrenia is associated with alterations in inhibitory inputs from SST/NPY-containing and CCK-containing subpopulations of GABA neurons and in the signaling via certain GABA A receptors that mediate synaptic (phasic) or extrasynaptic (tonic) inhibition. In concert with previous findings, these data suggest that working memory dysfunction in schizophrenia is mediated by altered GABA neurotransmission in certain DLPFC microcircuits.